Generative-AI-based game asset creation: developing a system for supporting game production brainstorming - Cavalcanti, Luiz Paulo S. B.; Bezerra, Pamela T. L.; Barros, Gabriella A. B. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais Estendidos do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2025.10149, 2025)
Introduction: Recent advances in generative AI have surprised the public by quickly generating text and images of good quality, impacting many entertainment industries, like the game industry. Despite concerns related to data privacy and plagiarism, generative AI can support artists and developers during the brainstorming process, enhancing creativity and performance. Objective: This research develops a system that integrates different generative AI technologies to assist game asset creation (text, image, and sound) all in one place. Developers can define, among other things, a protagonist’s concept art, generate associated NPCs (both image and text), create quests (text), and a short soundtrack (audio). Methodology or Steps: To develop the proposed solution, an initial study on the different generative AI models for different assets was conducted. This was followed by the system development using Python, Streamlit, and some APIs. Finally, a set of experiments was conducted to analyze the system’s capability to generate high-quality and diverse assets for a role-playing game. Results: The results demonstrate the system’s potential to facilitate the creative process by optimizing the prompt engineering process and combining multiple generative AI technologies in a single tool, offering a versatile solution for both small teams and larger studios.